An empirical testing of informational efficiency in Bangladesh capital market: Informational efficiency in Bangladesh capital market - Joarder, Munim; Ahmed, M.; Haque, T.; Hasanuzzaman, S. (Springer New York LLC, 2014)
We investigate how efficiently the stock market participants incorporate the information contained in money supply changes into stock prices in an emerging economy like Bangladesh. Of particular interest is to test how the changes inmonetary aggregates directly affect the stock prices through asset changes and indirectly through their effects on real economic activity. We have considered the monthly series of the real stock returns (P) and examine the relationship between stock returns and monetary aggregates from 1980 to 2008. We also include the exchange rate of US dollar against Bangladeshi Taka and industrial production index. The presence of cointegration between stock prices and monetary aggregates indicate long-run predictability of the Bangladesh stock market. The short-run dynamics between monetary aggregates and real stock return, relied on theoretically motivated long-run restrictions, are analyzed using an empirical structural VAR model. The dynamic response of the real stock returns to changes in macroeconomic variables (such as broad money supply, exchange rates), particularly its lagged responses to real economic activity generates inefficiency in the Dhaka Stock Exchange. The findings of this article indicate that informational inefficiency existsin the stock market of Bangladesh due to the presence of unidirectional causality. To be efficient, the infrastructure of the SEC should be modernized, revaluation of the net asset value of the companies should be audited by the affiliated firms of the SEC, demutualization should be done as early as possible, private placement, issue of preference share and book building methods must be under rule based. Insider trading should be strictly prohibited.